2012
DOI: 10.1155/2012/928643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin in the 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-Induced Mouse Model of Parkinson's Disease

Abstract: In this paper, the protective effect of the bioflavonoid quercetin on behaviors, antioxidases, and neurotransmitters in 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-(MPTP-) induced Parkinson's disease (PD) was investigated. Quercetin treatment (50 mg/kg, 100 mg/kg and 200 mg/kg body weight) was orally administered for 14 consecutive days. The results show that quercetin treatment markedly improves the motor balance and coordination of MPTP-treated mice. Significant increases were observed in the activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 19 publications
3
64
0
1
Order By: Relevance
“…In this study we found that the injection of MPTP increased nigral 4-HNE amount. These findings are consistent with the literature data [52,53]. In our study, the administration of DHA decreased the content of 4-HNE in the substantia nigra of DHA+MPTP group.…”
Section: Discussionsupporting
confidence: 94%
“…In this study we found that the injection of MPTP increased nigral 4-HNE amount. These findings are consistent with the literature data [52,53]. In our study, the administration of DHA decreased the content of 4-HNE in the substantia nigra of DHA+MPTP group.…”
Section: Discussionsupporting
confidence: 94%
“…Quercetin administration to neurons attenuated 1-methyl-4-phenylpyridinium (MMP) evoked microglia activation, which is a precursor for PD pathogenesis [124]. Studies have also shown that quercetin promises neuroprotection in PD mice model by stimulating glutathione peroxidase (GPx), superoxide dismutase (SOD), Na( + ), and K( + )-ATPase [141]. Quercetin suppressed cell death in PD cell model while its metabolite quercetin-3- O - β -glucuronide, due to its low absorption, did not affect cell viability [142].…”
Section: Polyphenols and Pharmacological Propertiesmentioning
confidence: 99%
“…Alternatively, quercetin may induce PON2 expression by activating estrogen receptors alpha (Galluzzo et al 2009), though this would need to be investigated further. Independent of the underlying mechanism(s), the ability of quercetin to induce PON2 may play a role in the reported neuroprotective actions of this polyphenol, which have been observed in vitro (Mercer et al 2005; Ossola et al 2009; Bournival et al 2009), as well as in vivo (Barcelos et al 2011; Lv et al 2012; Selvakumar et al 2012). In striatal astrocytes from PON2 +/+ mice (mixed gender), exposure for 24 h to quercetin abolished the increase in ROS levels caused by H 2 O 2 or DMNQ, and resulted in protection against the cytotoxicity of these oxidants.…”
Section: Modulation Of Pon2mentioning
confidence: 99%